The effect of CNT content and sintering temperature on some properties of CNT-reinforced MgAl composites - Islak Serkan; Küçük Özkan; Eski Özkan; Özorak Cihan; Akkaş Mehmet (National Library of Serbia, 2017)
Magnesium and its alloys are considered as an important material for modern light structures at the present time and therefore they have a wide area of usage especially in electronics, aircraft, and automotive industries. Its popularity increases further as a result of its production as a composite material. In this study, carbon nanotube (CNT) reinforced MgAl matrix composite materials were produced by using the hot pressing method. While 0.25 wt%, 0.50 wt%, 0.75 wt%, and 1.00 wt% CNT were added, 450?C, 500?C, and 550?C was selected as sintering temperatures. The effect of sintering temperature and amount of CNT on some properties of the composites was examined. Microstructure and phase composition of the materials were examined by using optical microscopy (OM), scanning electron microscope (SEM), X-ray diffraction (XRD), and energy-dispersive X-ray spectroscopy (EDS). The hardness of the composites was measured in Brinell. Relative densities of the materials were determined in accordance with Archimedes? principle. A dense and slightly porous structure was obtained based on both SEM images and density measurements. XRD analyses showed that there were Mg, Mg17Al12, and MgO phases in the composites. The reason for the absence of Al in graphics was that Al formed the solid solution by being dissolved in Mg. Also, the C peak could not be determined for CNT. The hardness of the composites increased with the increasing sintering temperature and CNT addition. The highest hardness value was measured as 88.45 HB10 with the addition of 1.00 wt% CNT at 550?C. Free distribution of CNT in the matrix caused this hardness increase.
Keywords: CNT; Chemical technology; MgAl alloys; TP1-1185; Hot press sintering.; Composites